Multiple taxa in the Phoma-complex associate with black elder (Sambucus nigra L.). Issue 1 (January 2016) - Walter, Hildrun; Muggia, Lucia; Fritscher, Michael; Holler, Alessandro; Horvat, Deborah; Guttenberger, Helmut; Simon, Uwe K.
Abstract: The fungus Boeremia sambuci-nigrae (formerly Phoma sambuci-nigrae ) causes the corymb wilt disease in elder ( Sambucus nigra L.). Here, we assessed the genetic diversity of fungi within the Phoma -complex which associate with commercially cultivated elder in Styria (Austria). We sampled leaves, corymb stalks and berries of elder trees in one organically and in four conventionally managed orchards. In each orchard an area was left untreated allowing a sampling of fungicide treated and untreated trees. Nineteen taxa in the Phoma -complex were isolated and identified based on ITS and LSU nucDNA sequences. One isolate is closely related to Chaetosphaeronema, whereas the majority of the strains belong to the genera Epicoccum and Boeremia in Didymellaceae . Six isolates are monophyletic with Boeremia sambuci-nigrae . The results indicate a varying effectiveness of fungicide treatment for the different fungal groups investigated. The diverse distribution of isolates among the sampling sites suggests the influence of treatment effects and possibly also of climatic conditions. Highlights: Phoma -related endophytes isolated from Styrian elder trees show a broad diversity. Didymellaceous fungi show a site-specific occurrence in diversity and number. Within Didymellaceae, Epicoccum, and Boeremia are the most frequently isolated taxa. Four isolates form a separate clade basal to Stagonosporopsis group.